2009
DOI: 10.1126/science.1170165
|View full text |Cite
|
Sign up to set email alerts
|

Late Pleistocene Demography and the Appearance of Modern Human Behavior

Abstract: The following resources related to this article are available online at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
716
2
10

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 864 publications
(769 citation statements)
references
References 31 publications
41
716
2
10
Order By: Relevance
“…These topics are non-exclusive and non-exhaustive, and they are intended to provide an initially broad set of targets for identifying external influences on tool use. In recent years, researchers have explored the relevance of the number of interacting individuals to the maintenance of traditions, showing that an increase in social contacts can allow for new ideas and techniques to be retained and spread more readily in a population [39][40][41][42]. The principle is not restricted to the human lineage [43], and wild orangutans and chimpanzees have been found to display increased complexity, success and frequency in tool use in increasingly social and higher population density settings [44][45][46].…”
Section: (B) Factors Promoting Captivity Biasmentioning
confidence: 99%
“…These topics are non-exclusive and non-exhaustive, and they are intended to provide an initially broad set of targets for identifying external influences on tool use. In recent years, researchers have explored the relevance of the number of interacting individuals to the maintenance of traditions, showing that an increase in social contacts can allow for new ideas and techniques to be retained and spread more readily in a population [39][40][41][42]. The principle is not restricted to the human lineage [43], and wild orangutans and chimpanzees have been found to display increased complexity, success and frequency in tool use in increasingly social and higher population density settings [44][45][46].…”
Section: (B) Factors Promoting Captivity Biasmentioning
confidence: 99%
“…The model predicts that the more costs can be borne, be it by direct benefits or by capacity of the population 6 , the more psychosensory biases will be materialized. There are some indications from the archeological record that iconic art production (figurative imagery, realistic art) is a mainly culturally transmitted behavior (paper submitted by the authors; also see Shennan 2001;Powell et al 2009), while the ability to experience and interpret art is not and is in fact predating art production just like the origin of female sensory biases leading to mate preferences sometimes predate exploitation (e.g. Ryan 1998).…”
Section: Self-exploitationmentioning
confidence: 99%
“…Ryan 1998). The process of gradual accumulation of innovative skills and knowledge as a consequence of cultural "cumulative adaptive evolution" (Henrich 2004, Powell et al 2009) also positively affects art production in the sense that it is less hindered by costs (i.e.…”
Section: Self-exploitationmentioning
confidence: 99%
“…Henrich's (2004) original model contained certain assumptions concerning the micro-level link between demography and complexity (e.g. payoff-biased social learning), but large-scale archaeological studies such as Powell et al (2009) can only test the outcome of this model, not the validity of the mechanisms. Derex et al (2013), Muthukrishna et al (2014) and all found that, as predicted, larger groups containing more individuals from whom to learn supported higher levels of cultural complexity in various tasks, including designing computerised fishing nets, knottying, and completing jigsaw puzzles.…”
Section: Demography Can Influence the Evolution Of Cultural Complexitymentioning
confidence: 99%